In a search for effective giant magnetoelectric coupling: Magnetically induced elastic resonance in Ni-Mn-Ga/P(VDF-TrFE) composites. (December 2022) - Martins, Pedro; Lima, Ana C.; L'vov, Victor A.; Pereira, Nélson; Sratong-on, Pimpet; Hosoda, Hideki; Chernenko, Volodymyr; Lanceros-Mendez, Senentxu
Highlights: This work offers a new route for the amplification of the magnetoelectric coupling in polymer-based 0–3 composites. The obtained unprecedented value of the ME coefficient at the resonance maximum is the highest one reported in the literature for 0–3 composites. The record-breaking ME effect was explained using theoretical modeling (magnetovolume strain inducing elastic wave resonance). Most importantly this work merges the benefits of 0–3 systems (room-temperature and greener processing, additive manufacturing compatibly and optimized mechanical features) and 2–2 systems (ME coupling coefficient in the order of V·cm −1 · Oe −1 ). Abstract: Poly(vinylidene fluoride-trifluoroethylene) (P(VDF-TrFE)) is a piezoelectric polymer suitable for applications in electromechanical and magnetoelectric (ME) systems. Ni-Mn-Ga alloys exhibit a giant magnetoelastic response related to their structural transformations of martensitic type, accompanied by noticeable volume changes. Together, in a thin film composite containing an ensemble of Ni-Mn-Ga particles (10 wt.%) distributed in the P(VDF-TrFE) piezopolymer, they ensure an unprecedented resonance amplification of the ME effect. Thus, a giant value of ME coefficient of 6.05 V·cm −1 · Oe −1 under AC magnetic drive field of 0.2 Oe and DC bias field of 1300 Oe is experimentally observed and discussed. The physical mechanism of the proposed ME response amplification has been explained theoretically through the volume magnetostriction of the magnetostrictive particles and resonant elastic oscillation of the piezoelectric polymer matrix. Graphical abstract: Image, graphical abstract